Water Production Rate in Comets - Deaza Rincon, Pedro Ignacio (Scientia et Technica, 2018)
In the atmosphere or coma of a comet, thedissociation of water gives the OH radical, that isdetectable by radioastronomical methods. Analyzingthe spectral emission line of 18 centimeters,corresponding to the hydroxyl OH, can be deduced itsrate of production, and, consequently, is possible inferthe rate of water production. The results of themeasurements carried in France with the Nancay radiotelescope, in Puerto Rico with the Arecibo RadioTelescope, in Hawaii with the J. C Maxwell telescopeand in Chile with ALMA radiotelescope, are allowingcurrently trying to build unified models of evolutionand activity cometary.